Paratextual Analysis of “Majmu 'Al-Masa'il” Aceh Manuscript : Study of Philology - Siti Raudhatul Hamdiyati; Pramono Pramono; Khairil Anwar (Politeknik Negeri Padang, 2021)
This article aims to analyze the paratext elements contained in the book Majmu 'Al-Masa'il. The term paratext is defined as a concept that helps readers interpret the main text of a book except for the body of the text, such as covers, pages, and marginal notes. Majmu 'Al-Masa'il is a book that contains the teachings of fiqh in paratextual analysis. However, this paper does not focus on discussing the teachings of fiqh but only focuses on the interpretation of the marginal notes on the pages of the book. Genette's paratext theory was used to analyze other material found in marginal notes on book pages. Paratext Genette is a theory used in analyzing main texts in philological studies.